2012
DOI: 10.1016/j.jtcvs.2011.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Repair of giant paraesophageal hernias routinely produces improvement in respiratory function

Abstract: Paraesophageal hernia has a significant effect on respiratory function, which is largely underappreciated. This study demonstrates that these repairs can be done safely and supports routine consideration for elective repair; older patients with borderline respiratory function may achieve substantial improvements in their respiratory status and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 21 publications
2
56
0
2
Order By: Relevance
“…Friction from the stomach moving in and out of the diaphragmatic hiatus can cause ulceration of the overlying gastric mucosa leading to upper gastrointestinal bleeding and chronic anaemia. The herniated stomach can also cause a mass effect in the posterior mediastinum leading to exertional dyspnea [35]. The annual risk of developing acute symptoms necessitating emergency surgery has been quoted as 1.1% per year [36].…”
Section: Other Symptoms From Ghhmentioning
confidence: 99%
See 4 more Smart Citations
“…Friction from the stomach moving in and out of the diaphragmatic hiatus can cause ulceration of the overlying gastric mucosa leading to upper gastrointestinal bleeding and chronic anaemia. The herniated stomach can also cause a mass effect in the posterior mediastinum leading to exertional dyspnea [35]. The annual risk of developing acute symptoms necessitating emergency surgery has been quoted as 1.1% per year [36].…”
Section: Other Symptoms From Ghhmentioning
confidence: 99%
“…In a number of cohort studies where patients were selected to have a GHH repair it has been reported that: 80% to 92% of preoperative symptoms resolve [2,40]; there is an improved gastro-intestinal quality of life [37,40,41]; there is an objective improvement in pulmonary function [35] and there is an objective improvecy towards a lower mean LOS pressure/tone, reduced LOS length and reduced intra-abdominal length of LOS contributing to the increased likelihood of GORD [22][23][24][25]28,30]. It is important to note that some patients with GHH have normal LOS pressures, which may explain why reflux is not always a major symptom in this group of patients [22,30].…”
Section: Management Of Gord In Patients With Ghhmentioning
confidence: 99%
See 3 more Smart Citations